Whisper of the blase revolution, mayhem, betrayal, glory and death - Durschmied, Erik (Hodder & Stoughton, 2001)
Progressing from the 18th to the 20th century, this work uses historical texts, eye witness accounts and interviews to provide a snapshot of history as shaped by revolution. Events covered include the French Revolution, the Red October rising and the activities of Che Guevara.